Examining farm financial management: How do small US farms meet their agricultural expenses? - Omobolaji Omobitan; Aditya R. Khanal (Journal of Risk and Financial Management, 2022)
Small farms in the US have significant challenges in financial management. This study examines how small farmers undertake farm financial management to meet their agricultural and farm-related spending and expenses. Using primary survey data from Tennessee, the study investigates the factors influencing the extent of use of five financing sources to meet the spending and expenses: cash/fund directly generated from the sale of agricultural products, farmer's past savings, farm household's off-farm income, income/incentives from government payments, and external loans. Using negative binomial regression estimation of generalized linear models, findings suggest that the decision on the use of financing sources is significantly influenced in general by age, education, income and land acreage holdings, off-farm work, and risk factors related to farmer or farm household. However, the associated factors and their effects on the extent of use are different depending on the financing source.
Keywords: 330; farm financial management; farm management; small farms; survival risk; savings; debt; off-farm incomes